IMPROVEMENT OF FOREIGN DIRECT INVESTMENTS STIMULATION MECHANISMS IN KAZAKHSTAN - A. Panzabekova,; M. Kolbayev,; G. Nyurlikhina, (Academic Journal of Physical and Chemical Sciences, 2019)
The purpose of the article is to develop proposals for improving the economic mechanisms for stimulating foreign direct investment (FDI) for the economy of Kazakhstan. The study is based on various methods of economic research: systemic and structural-functional analyzes, methods of statistical analysis, comparative and logical methods. The paper analyzes the approaches of a number of countries to attracting FDI and identifies features of the practice of their stimulation in developed and developing countries. A detailed description of the three-tier system for monitoring the investment climate in Kazakhstan is given, and positive trends in improving the mechanisms for attracting FDI are identified. However, factors that hinder the active involvement of financial assets have been identified. The paper proposes measures that will facilitate investors to invest in the manufacturing and innovation sectors of the economy of Kazakhstan. The results of the study can be used as a methodological basis for further deepening research on this issue.